B-type natriuretic peptide: a role in selection and follow up of the implantable cardioverter-defibrillator patient?. Issue 2 (13th January 2006) - Anderson, M
Abstract : B-type natriuretic peptide may have a role in predicting the risk of ICD therapy, identifying patients with deteriorating clinical status and allowing them to be selected for more detailed medical review and, if necessary, drug treatment